Studi Pemanfaatan Abu Sekam Padi (ASP) Sebagai Campuran Batako (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Rice husk ash is a pozzolan material which can be used as an additive in the manufacture of concrete, so that it potentially reduces the amount of cement in the material. This research aimed to determine the effect of rice husk ash addition on quality of brick making. The composition of rice husk ash added to the material was 10, 20, and 30% of the weight of cement used. Quality analysis was conducted on compressive strength, water absorption.Keywords: Compressive Strengt, Rice Husk Ash, and Water Absorption.